Knowledge on Multi-Drug Resistant Pathogens, Antibiotic Use and Self-Reported Adherence to Antibiotic Intake: A Population-Based Cross Sectional Survey From Pakistan - Arshad, Hafsa; Gillani, Ali Hassan; Akbar, Jamshaid; Abbas, Huda; Bashir Ahmed, Asma; Gillani, Syed Nouman Hassan; Anum, Rabeea; Ji, Wenjing; Fang, Yu (Frontiers in Pharmacology, 2022)
Objective: Surveying public awareness of antibiotic use and antibiotics can identify factors relevant to the design of effective educational campaigns. The aim of this study was to evaluate the knowledge, attitudes, and practices related to antibiotic use and multidrug-resistant pathogens in the general population in Pakistan. Research Design and Methods: Cross-sectional survey was conducted, using a 60 itemed structured questionnaire and recruited individuals by convenient sampling from the general population in the four provinces of the country. Descriptive statistics were used to evaluate the responses and the chi squared statistic was used to assess differences between groups. Results: The response rate was 87.6% (6,684 out of 7,631 individuals). Half of the respondents had received at least one prescription of antibiotics in the 6 months preceding the survey. Knowledge about antibiotic use, (39.8%) individuals scored above the mean (≥3) showed good knowledge about antibiotic use. Urban residents and male showed significant higher knowledge (p<0.001) about antibiotic use. Approximately 50% of the respondents correctly answered the question about antibiotic resistance. Of the 3,611 received antibiotics, 855 (23.7%) were indicated for cough, 497 (13.8%) for a sore throat, 335 (9.3%) for ear ache, 665 (18.4%) for a burning sensation during urination, 667 (18.4%) for wounds or soft tissue inflammation. MDR pathogen was perceived as an important topic by (4010) 60.1% of respondents. Conclusion: Participants were aware of the problem of multidrug-resistant pathogens and understood the responsibility of each individual to avoid the spread of these infectious agents.